Analysis of the Implementation of Exclusive Breastfeeding in Breastfeeding Mothers Covid 19 Pandemic Period - Deharnita; Sumarni, Tintin; Afconneri, Yudistira (POLTEKKES KEMENKES PADANG, 2023)
The impact of Covid on health services is that it is difficult for the community to obtain basic health services such as the implementation of the posyandu, classes for pregnant women, and classes for mothers under five. This results in low rates of maternal visits to posyandu, immunization, low achievement of family planning programs and exclusive breastfeeding, as well as prevention and control of stunting. Research purposes obtained description Implementation of Exclusive Breastfeeding for Breastfeeding Mothers During the Covid-19 Pandemic. Qualitative research design which aims to obtain an overview of the implementation of Exclusive Breastfeeding for Breastfeeding Mothers during the Covid-19 Pandemic, carried out in Solok City in 2021. Data were collected using in-depth interviews and data were processed and analyzed. The results showed that all mothers said that exclusive breastfeeding was very good. Most mothers said they were happy and satisfied if they could breastfeed their babies for up to 6 months. Most mothers said that the supporting factors in exclusive breastfeeding were beliefs and understanding about exclusive breastfeeding. the mother said that the inhibiting factor in breastfeeding was not smooth breastfeeding, stress. some mothers get information about exclusive breastfeeding from experienced people and are sought after on social media, most mothers expect information about exclusive breastfeeding to be obtained through social media. Based on the results of the study, it is suggested that you can design and create applications to increase the knowledge and abilities of mothers, especially about exclusive breastfeeding through tele-counseling and digital IEC.